Birth weight and gestational age on retinopathy of prematurity in discordant twins in China - Zong-Hua Wang; Yao-Yu Li; Zhi-Min Liu (International Journal of Ophthalmology, 2014)
AIM:To assess the relative effect of birth weight and gestational age on retinopathy of prematurity (ROP) using preterm twin pairs discordant for birth weigh in a tertiary neonatal intensive care unit in China.METHODS: Fifty-six discordant twin pairs of 112 preterm infants were retrospectively analyzed. The twin pairs were divided into two subgroups based on birth weight in each pair. The occurrence of ROP and severe ROP requiring treatment were compared between the lower birth weight infants and their co-twins with the higher birth weight. Some neonatal morbidities related to prematurity and neonatal characteristics were also compared between the twin pairs.RESULTS: Based on the univariate analysis, gestational age and birth weight were significantly associated with the occurrence and progression of ROP. But no significant differences in ROP between larger and smaller infants were observed in the twin-paired analysis. The incidence of neonatal morbidities regarding respiratory distress syndrome (RDS), patent ductus arteriosus (PDA), intraventricular hemorrhage (IVH), sepsis and neonatal characteristics regarding gender distribution, one- and five-minute Apgar score, postnatal steroid treatment, blood transfusion, supplemental oxygen therapy, and mechanical ventilation were not different between the twins. However, gestational age of ≤28wk was significantly associated with significantly higher rates of ROP and severe ROP.CONCLUSION: Gestational age is a better predictor of ROP than birth weight in the twin-paired study.